Yoga and psychiatric disorders: a review of biomarker evidence. (17th February 2021) - Bhargav, Hemant; George, Sanju; Varambally, Shivarama; Gangadhar, Bangalore Nanjundaiah
Abstract: Traditionally, yoga has been used as a means for spiritual growth but over the past two decades or so its therapeutic benefits in psychiatric disorders have been scientifically explored. Yoga has been shown to be useful as a mono-therapy in mild to moderate depression and as an adjuvant in several psychiatric disorders including schizophrenia, anxiety disorders, substance use disorders and Mild Cognitive Impairment. Furthermore, systematic attempts have been made to understand the biological correlates of yoga in these psychiatric disorders. Given that no psychiatric disorder has strong and established biomarkers, it is interesting that preliminary research has demonstrated significant changes in certain important biomarkers following regular yoga practice. In this brief review, we provide an update on the effects of yoga on biochemical, neuro-physiological and neuro-imaging related bio-markers in psychiatric disorders. Although findings and trends are promising, much more research is warranted to establish a definite biological basis for yoga in psychiatry.